Interactivity in online pension planners enhances engagement with retirement planning – but not for everyone. Issue 4 (12th August 2019) - Brüggen, Elisabeth Christine; Post, Thomas; Schmitz, Katharina
Abstract : Purpose: People around the world are not sufficiently capable or willing to engage in retirement planning. New technological tools have been proposed as a promising solution to foster involvement and consequently encourage retirement planning. This paper aims to test whether an interactive online pension planner can improve participants' behaviour, behavioural intentions, attitude, knowledge and perceived ease of use, usefulness and enjoyment. Design/methodology/approach: In collaboration with a company specialised in technologically advanced pension planners, three different versions of an online pension planner were created. The control condition only allowed participants to check their pension situation and the composition of future retirement income. In the medium interactivity level, participants could choose to modify certain variables affecting their pension income, on top of the features from the control. The highly interactive planner additionally included an interactive budget tool and showed whether the accumulated pension income was sufficient to cover the desired spending. Data were collected with the help of an online panel ( N = 285). Findings: This paper finds a positive effect of interactivity on behaviour within the planner, that is, the number of clicked options, as well as on participants' intention to check their personal pension situation in the upcoming three to six months. Moreover, this paper finds gender differences: male participants prefer a high level of interactivity, while women prefer a medium level. Research limitations/implications: An interesting modification to the current research design would be to use personal, self-relevant data in the online pension planner. Moreover, conducting the study in a computer laboratory could increase concentration on the task, and hence involvement. Next to gender, there might be other factors that possibly influence the results. It would be interesting to investigate other measures of behaviour such as the time spent on the pension planner. Further research should also study the effects of other features that shape user's perception of interactivity, which include human-to-human interactivity. Practical implications: The results show that technological services, such as advanced online pension planners, can positively affect engagement with retirement planning. Thus, pension providers are encouraged to use interactive online pension planners. The results with respect to gender suggest tailoring pension planners to match specific preferences of recipients. New service technologies provide novel opportunities to cater to individual differences by, for example, integrating less interactive features for women than for men in a pension planner. Moreover, cognitive involvement should be stimulated by integrating relevant, interesting and valuable information. Social implications: Lack of engagement with retirement planning is an important challenge to Western societies. People who do not sufficiently search for information about their expected pension benefits may encounter significant pension gaps resulting in detrimental welfare effects at retirement. This problem is enhanced by the fact that increasingly, the risks and responsibility for retirement planning are being shifted towards pension plan participants themselves. Thus, finding ways to increase engagement with retirement planning by making use of advances in service technologies brings benefits to society. Originality/value: First, this paper contributes to the customer engagement literature by studying how new technological interfaces improve user experiences, knowledge and engagement within the low involvement context of retirement planning. Second, this paper advances service research by zooming in on customer heterogeneity in using the technology-based online pension planner and studying the moderating effect of involvement and gender more closely. Third, this paper contributes to the financial services literature by studying how new service technologies can help to increase attitudes, knowledge and engagement with retirement planning.